Adherence to Short-course Pharmacotherapy in Adults with Irritable Bowel Syndrome. (July 2020) - Sherwin, LeeAnne B.; Deroche, Chelsea B.; Krisanabud, Poungkamon; Matteson-Kome, Michelle; Bechtold, Matthew; Ruppar, Todd
Irritable Bowel Syndrome (IBS), characterized by abdominal pain and bowel dysfunction, treatment focuses on alleviating symptoms. Adherence is crucial for pharmacologic management success. We examined 73 adult's objective adherence to rifaximin using the taxonomy for adherence. Demographic, quality of life (QOL), psychological distress, perceived stress, adverse childhood experiences (ACE), pain, and adherence data were collected. Impaired QOL, elevated psychological distress and perceived stress, and a significant number of ACE were reported at baseline. Average time to prescription initiation was 2.5 days. Once implemented, 92% missed midday dose and persisted 5 days beyond the prescribed dose. High-adherers reported lower pain levels post-rifaximin compared to low-adherers. Objective adherence was significantly lower than self-reported. Objective adherence was not predicted by above variables. Adherence to rifaximin is poor in those with IBS. Future research examining perceived barriers/facilitators toward rifaximin adherence may provide insight into patient-centered, modifiable targets for adherence interventions and improve patient-related outcomes.